THE EMERGENCY THREAT OF TEXT GENERATIVE ARTIFICIAL INTELLIGENCE IN ACCOUNTING EDUCATION - Ivana Ivana; Bonnie Soeherman (Program Studi Akuntansi FPEB UPI, 2024)
Artificial Intelligence (AI) technology is beginning to impact accounting education. Students may potentially rely entirely on AI, raising ethical and educational quality concerns. The research addresses the readiness of accounting study programs to face the AI phenomenon. The aim is to provide policy development references for aligning accounting education with AI technology. The research object is the accounting program at Pandawa University, which is a pseudonym. This research uses a qualitative approach with data acquisition methods through interviews, observation, and document analysis. The results showed that AI is allowed to be utilized by students as an aid tool. Second, AI only covers the intelligence of the human left brain, so the education process must also focus on developing right brain intelligence. Implications include realigning graduate profiles and accounting curriculum, providing digital literacy about AI to educators, and promoting ethics in the digital space to the academic community.